Steadiness of average incoming long wave radiation - GANGOPADHYAYA, M.; VENKATARAMAN, S. (MAUSAM, 1970)
Analysis of the pyrgeometer data on the incoming long wave sky radiation available in India shows that while there is variation in the mean value from month to month, the variation from hour to hour in a night and from year to year for the same month is quite small. The variations of the incoming long wave radiation run closely parallel to the variations in the precipitable water content of the atmosphere. As pyrgeometer observations are not available outside India, the net radiation data between the hours 2200 to 0300 LAT for a number of stations in Asian and European U.S.S.R., Canada, Australia, England and Europe are examined for the year 1966.From this study it is inferred that the night time variation in sky radiation is quite small even in other parts of the globe.